2017
DOI: 10.1038/srep44603
|View full text |Cite
|
Sign up to set email alerts
|

Modulated CH3NH3PbI3−xBrx film for efficient perovskite solar cells exceeding 18%

Abstract: The organic-inorganic lead halide perovskite layer is a crucial factor for the high performance perovskite solar cell (PSC). We introduce CH3NH3Br in the precursor solution to prepare CH3NH3PbI3−xBrx hybrid perovskite, and an uniform perovskite layer with improved crystallinity and apparent grain contour is obtained, resulting in the significant improvement of photovoltaic performance of PSCs. The effects of CH3NH3Br on the perovskite morphology, crystallinity, absorption property, charge carrier dynamics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 50 publications
(72 reference statements)
6
38
0
Order By: Relevance
“…Snaith's group found that perovskite material with hybrid halides such as CH 3 NH 3 PbI 3− x Cl x not only showed higher stability when processing in air but also had much longer carrier diffusion lengths compared with pure MAPbI 3 . MAPbI 3− x Br x and CH 3 NH 3 Br (MABr) additive‐treated MAPbI 3 materials have also been confirmed to have improved performance and stability …”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Snaith's group found that perovskite material with hybrid halides such as CH 3 NH 3 PbI 3− x Cl x not only showed higher stability when processing in air but also had much longer carrier diffusion lengths compared with pure MAPbI 3 . MAPbI 3− x Br x and CH 3 NH 3 Br (MABr) additive‐treated MAPbI 3 materials have also been confirmed to have improved performance and stability …”
Section: Introductionsupporting
confidence: 93%
“…Accordingly, the observed phenomena following the use of the MABr additive in this work are consistent with those reported in Ref. .…”
Section: Resultsmentioning
confidence: 74%
“…[6] In a planar PSC, hole-and/or electron-transporting layers are always introduced to manipulate the carrier behavior in the device. [1,[7][8][9][10][11][12][13][14][15][16][17][18][19] It can serve as an efficient hole-blocking layer at the interface between [6,6]-phenyl-C61-butyric acid methyl ester) (PCBM) and metal contact by its wide bandgap. [3][4][5] In addition to the tailoring role of the energy levels, the upper interfacial film can also act as a significant protecting layer for the perovskite layer.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, after doping, the per-ovskite band-gap was blue-shifted accordingly to the broadening of the band-gap of plain thin films after the addition of Cs + or Br À ions. [110][111][112] The perovskite with 0.9:1:0.1 ratio of CH 3 NH 3 I:PbI 2 :CsBr showed aP CE of 13.6 %, which is much highert han the 9.8 %v alue without doping.…”
Section: Caesium-doping In Hybrid Perovskitesmentioning
confidence: 96%
“…To solve these issues, in 2014 Figure 1. The crystalline structures of A) 2D and B, C) 3D perovskites; D) Schematic illustrations of (110), (002), ( 112) and (200) crystal planes from ap erpendicular view,f or perovskites composedo f( MAPbI 3 ) 1Àx (CsPbBr 3 ) x with x ranging from 0t o0 .2.Adapted and reprinted with permission. [97,116] of Cs-doping by replacing the organic cation in the MAPbI 3 structurew ith an inorganic cation.…”
Section: Caesium-doping In Hybrid Perovskitesmentioning
confidence: 99%